Brain microstructural injury occurs in patients with RRMS despite 'no evidence of disease activity'. Issue 9 (16th March 2018) - Harel, Asaff; Sperling, Dylan; Petracca, Maria; Ntranos, Achillefs; Katz-Sand, Ilana; Krieger, Stephen; Lublin, Fred; Wang, Zichen; Liu, Yangbo; Inglese, Matilde
Abstract : Objectives: The accuracy of 'no evidence of disease activity' (NEDA) in predicting long-term clinical outcome in patients with relapsing remitting multiple sclerosis (RRMS) is unproven, and there is growing evidence that NEDA does not rule out disease worsening. We used diffusion tensor imaging (DTI) to investigate whether ongoing brain microstructural injury occurs in patients with RRMS meeting NEDA criteria. Methods: We performed a retrospective study to identify patients with RRMS visiting our centre over a 3-month period who had undergone prior longitudinal DTI evaluation at our facility spanning ≥2 years. Patients meeting NEDA criteria throughout the evaluation period were included in the NEDA group, and those not meeting NEDA criteria were included in an 'evidence of disease activity' (EDA) group. Fractional anisotropy (FA) and mean diffusivity (MD) maps were created, and annual rates of change were calculated. Results: We enrolled 85 patients, 39 meeting NEDA criteria. Both NEDA and EDA groups showed longitudinal DTI worsening. Yearly FA decrease was lower in the NEDA group (0.5%, p<0.0001) than in the EDA group (1.2%, p=0.003), while yearly MD increase was similar in both groups (0.8% for NEDA and EDA, both p<0.01). There was no statistical difference in deterioration within and outside of T2 lesions. DTI parameters correlated with disability scores and fatigue complaints. Conclusions: White matter microstructural deterioration occurs in patients with RRMS over short-term follow-up in patients with NEDA, providing further evidence of the limitations of conventional measures and arguing for DTI in monitoring of the disease process.